Customer satisfaction in directed activities in municipal sports centers - Aparicio Chueca, P.; Elasri Ejjaberi, A.; Triadó Ivern, X. M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The aim of this work is to identify and analyze the factors that underlie the level of satisfaction of users of municipal sports centers that conduct directed activities and compare it with those users who do not use this service. Data were collected in a survey among users of municipal sports centers, of which 536 subjects stated that they carried out directed activities at the center. Women and users with a high school level are the ones who use these services the most. An applied factor analysis reveals three dimensions that contribute to satisfaction, in both cases, but the composition of each of them is different. Finally, the multiple regression analysis shows that a manager must pay attention, first of all, to the quality of the facilities and communication since they were the best predictor of satisfaction.